Dante Gabriel Rossetti’s déjà vu - McGhee, F (Indiana University Press, 2020)
This essay explores how the poetry of Dante Gabriel Rossetti engages with the experience of déjà vu, which was first treated as an object of sustained medical and psychological research in the late nineteenth century. Situating the poems in this context reveals the persistence and sophistication with which Rossetti represents “dreamy states” (as they were then known), as well as his influence on how they came to be studied and understood. Drawing attention to the close associations between déjà vu and imagination in the period, the essay goes on to suggest how this uncertain experience of knowing became the model for an effect Rossetti sought from his own poems: a dream-like commingling of presence and retrospect, strangeness and familiarity, cognition and recognition.